Neuronal loss and microgliosis are restricted to the core of Aβ deposits in mouse models of Alzheimer's disease. Issue 6 (25th May 2021) - Zhang, Jing; Wu, Na; Wang, Shubo; Yao, Zitong; Xiao, Fuchuan; Lu, Jing; Chen, Baian
Abstract: Amyloid‐β (Aβ) deposits, pathologic tau, and neurodegeneration are major pathological hallmarks of Alzheimer's disease (AD). The relationship between neuronal loss and Aβ deposits is one of the fundamental questions in the pathogenesis of AD. However, this relationship is controversial. One main reason for the conflicting results may be the confounding effects of pathologic tau, which often coexists with Aβ deposits in the brains of AD patients. To clarify the relationship between neuronal loss and Aβ deposits, mouse models of AD, which develop abundant Aβ deposits in the aged brain without pathologic tau, were used to examine the co‐localization of NeuN‐positive neurons, NF‐H‐positive axons, MBP‐positive myelin sheaths, and Aβ deposits. Neuronal loss, as measured by decreased staining of the neuronal cell body, axon, and myelin sheath, as well as the IBA‐1‐positive microglia, was significantly increased in the core area of cerebral Aβ deposits, but not in adjacent areas. Furthermore, neuronal loss in the core area of cerebral Aβ deposits was correlated with Aβ deposit size. These results clearly indicate that neuronal loss is restricted to the core of Aβ deposits, and this restricted loss probably occurs because the Aβ deposit attracts microglia, which cluster in the core area where Aβ toxicity and neuroinflammation toxicity are restrained. These findings may contribute to our understanding of the relationship between neuronal loss and Aβ deposits in the absence of pathologic tau. Abstract : Neuronal loss is restricted to the core of Aβ deposits, and this restricted loss probably occurs because the Aβ deposit attracts microglia, which cluster in the core area where Aβ toxicity and neuroinflammation toxicity are restrained.